Formation of energetic electron butterfly distributions by magnetosonic waves via Landau resonance. Issue 7 (4th April 2016) - Li, Jinxing; Ni, Binbin; Ma, Qianli; Xie, Lun; Pu, Zuyin; Fu, Suiyan; Thorne, Richard M.; Bortnik, Jacob; Chen, Lunjin; Li, Wen; Baker, Daniel N.; Kletzing, Craig A.; et al.
Abstract: Radiation belt electrons can exhibit different types of pitch angle distributions in response to various magnetospheric processes. Butterfly distributions, characterized by flux minima at pitch angles around 90°, are broadly observed in both the outer and inner belts and the slot region. Butterfly distributions close to the outer magnetospheric boundary have been attributed to drift shell splitting and losses to the magnetopause. However, their occurrence in the inner belt and the slot region has hitherto not been resolved. By analyzing the particle and wave data collected by the Van Allen Probes during a geomagnetic storm, we combine test particle calculations and Fokker‐Planck simulations to reveal that scattering by equatorial magnetosonic waves is a significant cause for the formation of energetic electron butterfly distributions in the inner magnetosphere. Another event shows that a large‐amplitude magnetosonic wave in the outer belt can create electron butterfly distributions in just a few minutes. Key Points: Electron butterfly distributions of 100 keV are quickly formed in the radiation belts Electron butterfly distributions are observed in direct association with magnetosonic waves Numerical simulations produce butterfly distributions similar to the observations